PENGARUH KARAKTERISTIK INDIVIDU, MOTIVASI KERJA DAN KOMITMEN KERJA TERHADAP KINERJA PEGAWAI - Andi Karmilawati; Murdjadi Kamaluddin; Endro Sukotjo (Pascasarjana Universitas Halu Oleo, 2018)
This study aims to test and analyze: (1). Effect of individual characteristics on the performance of employees of the Kolaka District Financial and Asset Management Agency, (2). The effect of work motivation on the performance of employees of the Kolaka District Financial and Asset Management Agency, and (3). Effect of work commitment on the performance of employees of the Regional Financial and Asset Management Agency of the Regency of Kolaka. This study uses employee respondents as many as 53. While the data analysis uses descriptive analysis and inferential analysis Multiple Linear Regression using SPSS software.The results of this study are (1). Individual characteristics have a significant effect on the performance of employees of the Kolaka District Financial and Asset Management Agency, (2). Work motivation has a significant effect on the performance of employees of the Kolaka District Financial and Asset Management Agency, and (3). Work commitment has a significant effect on the performance of employees of the Regional Financial and Asset Management Agency in Kolaka Regency.Keywords: individual characteristics, work motivation, work commitment and performance